Influence of poles on equioscillation in rational approximation - Blatt, H.-P. (Український математичний журнал, 2006)
The error curve for rational best approximation of f ∈ C[−1, 1] is characterized by the well-known equioscillation property. Contrary to the polynomial case, the distribution of these alternations is not governed by the
equilibrium distribution. It is known that these points need not to be dense in [−1, 1]. The reason is the influence
of the distribution of the poles of the rational approximants. In this paper, we generalize the results known so
far to situations where the requirements for the degrees of numerators and denominators are less restrictive. Крива похибок для раціонального найкращого наближення f∈C[−1,1] характеризується відомою властивістю еквіосциляцій. На відміну від поліноміального випадку розподіл цих змін знаку не визначається рівноважним розподілом. Відомо, що ці точки не обов'язково мають бути щільними в [−1,1], що зумовлено впливом розподілу полюсів раціональних наближень. У даній роботі узагальнено відомі результати на випадки, де на степені чисельників та знаменників накладаються менш жорсткі умови.